2004
DOI: 10.1111/j.1471-4159.2004.02527.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal expression of myeloperoxidase is increased in Alzheimer's disease

Abstract: Myeloperoxidase, a heme protein expressed by professional phagocytic cells, generates an array of oxidants which are proposed to contribute to tissue damage during inflammation. We now report that enzymatically active myeloperoxidase and its characteristic amino acid oxidation products are present in human brain. Further, expression of myeloperoxidase is increased in brain tissue showing Alzheimer's neuropathology. Consistent with expression in phagocytic cells, myeloperoxidase immunoreactivity was present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
208
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(225 citation statements)
references
References 64 publications
12
208
2
3
Order By: Relevance
“…A great deal of attention has been given to the role of peroxide-mediated and metal-catalyzed oxidative stress in Alzheimer's disease (54), but far less is known about the possible role of hypochlorite. Although detailed characterization of the effect of hypochlorite on Aβ 1-42 is outside the scope of the current study, the high expression of myeloperoxidase in the brains of sufferers of Alzheimer's disease and the localization of this enzyme in amyloid plaques suggest that hypochlorite oxidation of Aβ 1-42 is likely to occur in vivo (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of attention has been given to the role of peroxide-mediated and metal-catalyzed oxidative stress in Alzheimer's disease (54), but far less is known about the possible role of hypochlorite. Although detailed characterization of the effect of hypochlorite on Aβ 1-42 is outside the scope of the current study, the high expression of myeloperoxidase in the brains of sufferers of Alzheimer's disease and the localization of this enzyme in amyloid plaques suggest that hypochlorite oxidation of Aβ 1-42 is likely to occur in vivo (5).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). During inflammation, hypochlorite production is accompanied by additional stresses, which are themselves capable of inducing protein misfolding (e.g., increased temperature and lowered pH); it is, therefore, not surprising that, in a large number of diseases [e.g., atherosclerosis (4), Alzheimer's disease (5,6), age-related macular degeneration (7), and arthritis (8)], inflammatory pathology is associated with the accumulation of misfolded proteins. α 2 -Macroglobulin (α 2 M) is a highly abundant secreted protein that is best known for its ability to trap proteases (9); α 2 M can, however, interact with a broad range of molecules, and consequently, many other biological roles have been suggested, including targeting cytokines for clearance, sequestration of zinc, and opsonization of bacteria (reviewed in ref.…”
mentioning
confidence: 99%
“…10,[15][16][17][18][19] Until recently, phagocytic blood cells were thought to be the only cellular sources of MPO. However, recent studies 18,20,21 have shown that several cell types, including neuronal cells, express MPO under certain pathological conditions. Also, MPO is not expressed in healthy brain parenchyma but is expressed in several neurodegenerative diseases, such as Alzheimer's disease and PD.…”
mentioning
confidence: 99%
“…Also, MPO is not expressed in healthy brain parenchyma but is expressed in several neurodegenerative diseases, such as Alzheimer's disease and PD. 20,22,23 However, the precise roles of MPO and the underlying mechanisms responsible for its action have not been determined.…”
mentioning
confidence: 99%
“…Подтверждением этого является повышение в гиппокампе уровня 3-хлортирозина и битирозина -продуктов окисления за счёт катализируемой МПО реакции [27].…”
Section: возможные пути генерации афк при болезни альцгеймераunclassified